MITOS MASKULINITAS SEBAGAI KONSEP KONTEN PRODUK KECAP ABC DI MEDIA SOSIAL INSTAGRAM (STUDI KASUS: KONTEN â€AKADEMI SUAMI SEJATIâ€) - Indrayana, Andika; Putri Mardianti, Nurmala (Institut Seni Indonesia Yogyakarta, 2020)
Akademi Suami Sejati is a part of the theme used by Kecap ABC in their commercial campaign on Instagram. The theme aims at promoting gender equality in domestic field illustrated by a husband contributing in the household cooking activity as a means to build harmony. By means of this theme, diverse masculine images are represented using visual languages in many contents. This research objective was to identify and interprete the myth of masculinity in the Instagram content to get the structures of and relation between the myths and gender discourses. Roland Barthes? theory on signs levels and his seven methods of interpretation were employed in studying the visual objects identified. The research showed that: 1) the masculine images represented the idea of gender equality without demeaning men?s image of masculinity. 2) masculine image is identical to the Javanese concept ?dadi wong? (becoming a gentleman) and ?dadi modern? (becoming a modern man) in Javanese culture perspective.